Potential Conflict of Authority Among State High Institutions: A Study of Indonesian Constitutional Law - Sarji Sarji; Azis Budianto (CV. Green Publisher Indonesia, 2026)
Conflict authority between body and institution tall country is consequence the logical basis for implementing the principles of separation of powers and checks and balances in the Indonesian constitutional system following the amendment to the 1945 Constitution of the Republic of Indonesia. The increasingly complex distribution of authority, accompanied by the emergence of independent institutions, has the potential to lead to overlapping authority and differences in the interpretation of constitutional norms. This study aims to analyze the construction of authority of state institutions, identify potential conflicts of authority, and examine the mechanisms for resolving them from the perspective of Indonesian constitutional law. The research method used is normative legal research with a statutory, conceptual, and case approach, through an analysis of laws and regulations, legal literature, and Constitutional Court decisions related to disputes over the authority of state institutions. The results of the study indicate that the potential for conflict of authority caused by ambiguity norm, overlapping regulations and the dynamics of legal politics in state governance practices. The Constitutional Court plays a strategic role in resolving authority disputes, but its effectiveness still faces challenges. This study offers a constitutional ambiguity approach as a basis for analysis and recommends strengthening normative clarity and harmonizing regulations to minimize authority conflicts.